Stabilisation of Pb in Pb smelting slag-contaminated soil by compost-modified biochars and their effects on maize plant growth (2015)
Compost has been used to stabilise lead (Pb) in soil. However, compost contains a high level of dissolved organic matter (DOM) which may make Pb bioavailable in plant and thereby limiting its effectiveness and application. Addition of biochar to compost can reduce this effect. Rice husk (RH) and Cashew nut shell (CNS) biochars and compost-modified biochars were used in comparison to compost for stabilizing Pb in lead smelting slag (LSS)-contaminated soil (Pb = 18,300 mg/kg) in Nigeria. Efficiency of Pb stabilisation in control and amended soils was assessed using CaCl2 batch leaching experiment and plant performance. In pot experiments, maize plant was grown on the contaminated soil and on soil treated with minimum and optimum doses of the amendments singly and in combination for 6 weeks. Agronomical and chemical parameters of the plants were measured. CaCl2-extractable Pb in the untreated soil was reduced from 60 mg/kg to 0.55 mg/kg in RHB amended soils and non-detectable in other amended soils. RH-biochar/compost increased plant height, number of leaf and leaf area more than the others. Similarly, at minimum rate, it reduced root and shoot Pb by 91% and 86.0% respectively. Compost-modified rice husk biocharstabilised Pb in lead smelting slag contaminated soil reduced Pb plant uptake and improved plant growth. Lead stabilisation through the use of rice husk biochar with compost may be a green method for remediation of lead smelting slag-contaminated soil.